EXPERIMENTAL STUDY OF DIAMOND CRYSTALLIZATION IN CARBONATE-CARBON SYSTEMS IN CONNECTION WITH THE PROBLEM OF DIAMOND GENESIS IN MAGMATIC AND METAMORPHIC ROCKS - Pal'yanov Yu.N.; Sokol A.G.; Borzdov Yu.M.; Sobolev N.V. (My University, 1998)
Diamond crystallization in carbonate-carbon systems was studied on a "split sphere" device BARS at P = 7 GPa and T = 1700-1750°C (experiment time 18.5 h). It has been established that the heterogeneous nucleation of diamond in the studied systems is realized both at the melt-graphite interface and in the bulk of a carbon-saturated carbonate melt. Regular sequences of the catalytic activities of alkali and alkali-earth carbonates have been determined - Li2CO3 >Na2CO3 >K2CO3 >Cs2CO3 and CaMg(CO3)2>CaCO3 >MgCO3> SrCO3, respectively. It is experimentally shown that diamond nucleation strongly depends on kinetic factors. A possible decrease in the minimum PT-parameters of diamond synthesis in carbonate-carbon systems is justified. Analysis of the results on diamond synthesis together with petrological data suggests that carbonate and carbonate-silicate melt-fluids are the most probable medium of natural diamond formation in deep magmatic and metamorphic processes.